2014
DOI: 10.1080/17461391.2014.905984
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of sailing performance in youth dinghy sailing

Abstract: This study aimed to determine indicators of sailing performance in 2 (age) groups of youth sailors by investigating the anthropometric, physical and motor coordination differences and factors discriminating between elite and non-elite male optimist sailors and young dynamic hikers. Anthropometric measurements from 23 optimist sailors (mean ± SD age = 12.3 ± 1.4 years) and 24 dynamic youth hikers (i.e. Laser 4.7, Laser radial and Europe sailors <18 years who have to sail the boat in a very dynamic manner, due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
(32 reference statements)
1
18
1
1
Order By: Relevance
“…We attribute this circumstance to the same reason defined for the hand strength tests [25]. The results in manual grip strength values were much lower compared to another study in elite sailors in the Optimist (31.4 ± 4 vs. 24.3 ± 4.7; 31.4 ± 4 vs. 22.8 ± 4.4) and Laser (54.6 ± 3.6 vs. 36.6 ± 6.9; 54.6 ± 3.6 vs. 35.2 ± 6.2) classes [26]. It must be taken into account that this study presents the average value of the right and left hand, and that the average age of the Optimist and Laser class groups was 12.3 ± 1.4 and 16.5 ± 1.6 years, respectively.…”
Section: Discussioncontrasting
confidence: 75%
“…We attribute this circumstance to the same reason defined for the hand strength tests [25]. The results in manual grip strength values were much lower compared to another study in elite sailors in the Optimist (31.4 ± 4 vs. 24.3 ± 4.7; 31.4 ± 4 vs. 22.8 ± 4.4) and Laser (54.6 ± 3.6 vs. 36.6 ± 6.9; 54.6 ± 3.6 vs. 35.2 ± 6.2) classes [26]. It must be taken into account that this study presents the average value of the right and left hand, and that the average age of the Optimist and Laser class groups was 12.3 ± 1.4 and 16.5 ± 1.6 years, respectively.…”
Section: Discussioncontrasting
confidence: 75%
“…The research demonstrated that participating in ice hockey, swimming, and artistic gymnastics improved specific aspects of motor coordination. However, there is a versatility in motor coordination experiences during childhood and adolescence that has been shown to be a strong predictor of later athletic success [2][3][4][5][6]. Therefore, it is important that youth training programs include practice involving a variety of motor coordination characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…This is because motor coordination has been shown to be a strong predictor of athletic success in childhood and adolescence [2][3][4][5][6]. Motor coordination has been described as a relatively stable general physical construct that includes various aspects of motor ability [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that motor skills and motor performance are powerful indicators of children's health conditions and success in sports (Vandorpe et al, 2012a;Callewaert et al, 2015;Pion et al, 2015). It is evident that there are several factors that affect motor performance, one of which is the participation in sports.…”
Section: Introductionmentioning
confidence: 99%